Comparative studies of essential oils from Matricaria recutita L. - O. I. Panasenko; V. M. Odyntsova; O. M. Denysenko; V. I. Mozul; V. V. Holovkin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work is to determine the component composition of the essential oil of medicinal chamomile, grown on the educational and research site of medicinal plants of Zaporizhzhia State Medical and Pharmaceutical University (ZSMPHU), and commercial essential oil that was purchased via the Internet.